2021
DOI: 10.3390/biomedicines9111622
|View full text |Cite
|
Sign up to set email alerts
|

Mitoxantrone-Loaded Nanoferritin Slows Tumor Growth and Improves the Overall Survival Rate in a Subcutaneous Pancreatic Cancer Mouse Model

Abstract: Pancreatic cancer (PC) represents an intriguing topic for researchers. To date, the prognosis of metastasized PC is poor with just 7% of patients exceeding a five-year survival period. Thus, molecular modifications of existing drugs should be developed to change the course of the disease. Our previously generated nanocages of Mitoxantrone (MIT) encapsulated in human H-chain Ferritin (HFt), designated as HFt-MP-PASE-MIT, has shown excellent tumor distribution and extended serum half-life meriting further invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…For instance, the effects of SPIONs coated with curcumin and multifunctionalized magnetic iron oxide nanoparticles containing an anti-CD47 antibody, as well as the chemotherapeutic agent, gemcitabine, have been the subjects of former research [ 20 , 21 ]. However, MTO, a cytostatic drug used for cancer therapy and multiple sclerosis treatment with a potency up to 20,000 times higher than that of gemcitabine, has shown promising preclinical results for the treatment of pancreatic cancer [ 22 , 23 , 24 , 25 ]. Nevertheless, MTO did not show a significant response rate in a phase II clinical study including patients with advanced pancreatic carcinoma, as one of the main therapeutic limitations were dose-dependent hematologic side effects [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the effects of SPIONs coated with curcumin and multifunctionalized magnetic iron oxide nanoparticles containing an anti-CD47 antibody, as well as the chemotherapeutic agent, gemcitabine, have been the subjects of former research [ 20 , 21 ]. However, MTO, a cytostatic drug used for cancer therapy and multiple sclerosis treatment with a potency up to 20,000 times higher than that of gemcitabine, has shown promising preclinical results for the treatment of pancreatic cancer [ 22 , 23 , 24 , 25 ]. Nevertheless, MTO did not show a significant response rate in a phase II clinical study including patients with advanced pancreatic carcinoma, as one of the main therapeutic limitations were dose-dependent hematologic side effects [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, we have demonstrated that the ability of the human H-type ferritin (HFt) to bind to and being internalized through the transferrin receptor 1 (CD71 or TfR1) could be exploited to load different chemotherapeutic drugs into the ferritin cavity and deliver them to the cancer cells that often overexpress CD71 [ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] ] [ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] ] [ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] ]. Herein, we propose a first-in-class nanoparticle named The-0504 that incorporates in a single formulation many advantages of each of the above classes of cancer therapeutics, and at the same time has been carefully designed to minimize hurdles.…”
Section: Introductionmentioning
confidence: 99%